A review of congenital heart defects in children with Trisomy 21 over a 5-year period at Charlotte Maxeke Johannesburg Academic Hospital - Mahomed, Raeesa Moosa Kara (My University, 2021)
Background: In the first ten years of life, mortality in Trisomy 21 (T21) is strongly associated with the presence of Congenital Heart Defects (CHDs). There is currently a lack ofl ocal and regional data regarding the prevalence, management and outcomes of children with T21 and CHDs. Objectives: To describe the prevalence, type and frequency of CHDs and revie winter ventions (cardiac catheterisation and surgery) and survival post-surgery of children with CHDs in the T21 population at a South African facility ,the Charlotte Maxeke Johannesburg Academic Hospital (CMJAH) Paediatric Cardiology Unit (PCU). Methods: A retrospective, crosssectional, observational review of 177 participants at CMJAH PCU between January 2013 to December 2017 was performed. Data collected from the PCU data base and clinical records included: demographics, echocardiographic diagnosis, details of Diagnostic Cardiac Catheterisation (DCC), Interventional Cardiac Catheterisation (ICC) and surgery required and performed, age at diagnosis and intervention as well as survival post-surgery. Results: There were 128 participants with laboratory-confirmed T21 and CHD on echocardiography meeting inclusion criteria. The majority of participants were female (56.0%) and African (97.0%). The median age at presentation was six (IQR9.75) months. The prevalence of CHDs was 77/128 (60.2%) and 58/77 (75.3%) had a single CHD. The most frequent CHD was an Atrioventricular Septal Defect (AVSD) (38) (with or without another associated CHD) .DCC was required in 60/77 (77.9%) participants and 25/60 (41.6%) were performed. The median age at DCC was 15 (IQR 15) months. One participant with isolated PDA required and under went successful ICC for PDA closure at 17 months. Surgery was required in 60/77 (77.9%) of participants, while 15/60 (25.0%) surgeries were performed. Almost half of DDCs and surgeries not performed were due to participants lost to follow up (40% and 45% respectively). The median age at first surgery was 31 (IQR 24) months. The most common surgery was an AVSD repair (73%). Post-surgery survival was 93.3% at hospital discharge, 3-week and 6-month follow-up and 86.7% at 1-year follow-up . Conclusion: The prevalence, type and frequency of CHDs in the CMJAH T 21 population is comparable to global data. The age at presentation was not optimal for early intervention, and there was further delay in catheterisation and surgery. Survival post-surgery compares favourably with other centres even though surgery was performed at a much later age than the age recommended for best outcome (sixmonths). Early screening , diagnosis and intervention can prevent morbidity, mortality due to CHDs and may decrease the financial burden on the healthcare system.
A research report submitted to the School of Paediatrics and Child Health, Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, inpartial fulfilment of the requirements for the degree of Master of Medicine